Effects of applying preslaughter feed withdrawal at the abattoir on behaviour, blood parameters and meat quality in pigs. (September 2016) - Dalla Costa, F.A.; Devillers, N.; Paranhos da Costa, M.J.R.; Faucitano, L.
Abstract: To study the effects of starting time of feed withdrawal on behaviour during loading and lairage, and meat quality (pH, colour and drip loss) in pigs, a total of 700 pigs were distributed into two groups. One group (FARM) was fasted for 18 h at the farm before transport and for 6 h before slaughter (including 2 h transport and 4 h lairage), while for the other group (PLANT) fasting time started at the departure from the farm (2 h transport plus 22 h lairage). Total fasting time was 24 h before slaughter for both groups. Fasting treatments did not influence blood parameters. PLANT pigs had longer fights ( P  < 0.05) than FARM pigs during lairage and produced darker ( P  = 0.02) and drier ( P  = 0.03) loins. Based on the results of this study, it may be preferable to commence feed withdrawal at the farm.